Subsequent primary malignancies and acute myelogenous leukemia transformation among myelodysplastic syndrome patients treated with or without lenalidomide. (20th April 2016) - Rollison, Dana E.; Shain, Kenneth H.; Lee, Ji‐Hyun; Hampras, Shalaka S.; Fulp, William; Fisher, Kate; Al Ali, Najla H.; Padron, Eric; Lancet, Jeffrey; Xu, Qiang; Olesnyckyj, Martha; Kenvin, Laurie; et al.
Abstract: The few studies that have examined rates of acute myeloid leukemia (AML) transformation in lenalidomide‐treated myelodysplastic syndrome (MDS) patients have been limited to deletion 5q MDS. The association between lenalidomide and subsequent primary malignancies (SPMs) in MDS patients has not been evaluated previously. We conducted a retrospective cohort study to evaluate the risk of both SPM and AML in association with lenalidomide. A cohort of MDS patients ( n = 1248) treated between 2004 and 2012 at Moffitt Cancer Center were identified, and incident cases of SPM and AML transformation were ascertained. Using a nested case–control design, MDS controls were 1:1 matched to SPM ( n = 41) and AML ( n = 150) cases, on age and date of MDS diagnosis, gender, follow‐up time, IPSS, and del (5q). Associations between lenalidomide and (1) SPM incidence and (2) AML transformation were estimated with hazards ratios (HR) and 95% confidence intervals (CIs) in the cohort and odds ratios (OR) in the case–control analysis. SPM incidence did not differ significantly between cohort MDS patients treated with (0.7 per 100 person‐years) or without lenalidomide (1.4 per 100 person‐years) (HR = 1.04, 95% CI = 0.40–2.74), whereas a significantly reduced SPM risk was observed in the case–control sample (OR = 0.03, 95% CI = <0.01–0.63). Lenalidomide was not associated with AML transformation in the cohort analysis (HR = 0.75, 95% CI = 0.44–1.27) or in the case–control analyses (OR = 1.16, 95% CI = 0.52–2.56), after adjustment for potential confounders. Lenalidomide was not associated with increased risk of SPM or AML transformation in a large cohort of MDS patients mostly including nondeletion 5q MDS. Abstract : In a retrospective cohort study of myelodysplastic syndrome (MDS) patients ( n = 1248), conducted at Moffitt Cancer Center, lenalidomide was not associated with subsequent primary malignancies (SPMs) incidence in the MDS cohort (HR = 1.04, 95% CI = 0.40–2.74), whereas a significantly reduced SPM risk was observed in the case–control sample (OR = 0.03, 95% CI = <0.01–0.63). Lenalidomide was not associated with acute myeloid leukemia (AML) transformation in the cohort analysis (HR = 0.75, 95% CI = 0.44–1.27) or in the case–control analyses (OR = 1.16, 95% CI = 0.52–2.56), after adjustment for potential confounders. In conclusion, lenalidomide was not associated with increased risk of SPM or AML transformation in a large cohort of MDS patients mostly including nondeletion 5q MDS.